Tubularized incised plate urethroplasty for distal hypospadias: A literature review - Luis Henrique P Braga (Indian Journal of Urology, 2008)
The tubularized incised plate (TIP) urethroplasty or Snodgrass procedure has gained worldwide acceptance for distal hypospadias repair due to its low complication rate, good cosmetic result, and technical simplicity. As a result, several articles have been published concerning various aspects and subtle variations of this procedure. The aim of this review is to critically and systematically analyze the published complication rates of TIP repair for distal hypospadias in children. We also reviewed the surgical modifications that have been introduced to the original technique and discussed the potential impact on the final outcome of the Snodgrass procedure.